Importance Performance Analysis of MSME’s Digitalization Strategy to Increase Competitiveness Post COVID-19 - Nizwan Zukhri; Nanang Wahyudin; Maya Yusnita (AFEBI Management and Business Review, 2023)
In the post-Covid-19 situation, the Micro, Small and Medium Enterprises (MSME) sector needs serious attention from the government because it is the largest contributor to GDP and can be a factor in labor recruitment. To revive the performance of MSMEs in Pangkalpinang City which experienced a slump as a result of the Covid-19 pandemic, this study aims to produce a model for increasing the competitiveness of MSMEs globally during the Covid-19 pandemic as an effort to revive MSMEs through financial technology, digital marketing and digital leadership in MSMEs. in the city of Pangkalpinang, Bangka Belitung Islands, Indonesia. This research uses mixed research methods which is a combination of qualitative and quantitative research methods with the number of samples in this study is 100 respondents who are SMEs in Pangkalpinang City. The sampling technique in this research is accidental sampling. The analysis used is Importance Performance Analysis (IPA). The results of the study show that the implementation of financial technology, digital marketing and digital leadership on MSMEs in Pangkalpinang City is expected to be accelerated, this can be seen from the results of research which show that the majority of MSMEs have implemented financial technology such as mobile payments and digital banking. The analysis used is Importance Performance Analysis (IPA). The results of the study show that the implementation of financial technology, digital marketing and digital leadership on MSMEs in Pangkalpinang City is expected to be accelerated, this can be seen from the results of research which show that the majority of MSMEs have implemented financial technology such as mobile payments and digital banking. The analysis used is Importance Performance Analysis (IPA). The results of the study show that the implementation of financial technology, digital marketing and digital leadership on MSMEs in Pangkalpinang City is expected to be accelerated, this can be seen from the results of research which show that the majority of MSMEs have implemented financial technology such as mobile payments and digital banking.